The genus Amorphophallus Blume ex Decaisne (Araceae - Thomsonieae) in Java - Yuzammi, Yuzammi (REINWARDTIA, 2009)
An Alpha-taxonomic account of Amorphophallus Blume ex Decaisne in Java including key identification to the species is presented. Eight species are recognized in Java, of which five species are endemic. Full description as well as the usages of some species as source of starch are presented.